2023
DOI: 10.1055/a-2033-8632
|View full text |Cite
|
Sign up to set email alerts
|

Taming Challenging Radical-Based Convergent Paired Electrolysis with Dual-Transition-Metal Catalysis

Abstract: The past few years has witnessed the renaissance of electrochemistry in organ-ic synthesis. This green technology replaces chemical oxidants or reductants with inexpensive electricity. Paired electrolysis refers to processes where reac-tions at both electrodes are desirable. It maximizes the energy economy by avoiding the waste of electrical power on sacrificial reactions. Convergent paired electrolysis is a special case, where reactive intermediates are generated simultaneously at both electrodes and then cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
1
1
0
Order By: Relevance
“…This finding suggested that the nascent transient radical Int-3 generated via radical decarboxylation rapidly reacted with the double bond in the substrate to produce Int-4 . More importantly, this reaction outcome is also consistent with the diffusible radical mechanism of this radical-based convergent paired electrolysis, in which the radical capture by the intermediates (vinyl nickel complex, also can be viewed as persistent radical species in the present work) generated at the counter electrode would be the most challenging step of the reaction. , …”
Section: Results and Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This finding suggested that the nascent transient radical Int-3 generated via radical decarboxylation rapidly reacted with the double bond in the substrate to produce Int-4 . More importantly, this reaction outcome is also consistent with the diffusible radical mechanism of this radical-based convergent paired electrolysis, in which the radical capture by the intermediates (vinyl nickel complex, also can be viewed as persistent radical species in the present work) generated at the counter electrode would be the most challenging step of the reaction. , …”
Section: Results and Discussionsupporting
confidence: 84%
“…In particular, the spatial separation of the anode and cathode, the essential feature of electroorganic synthesis, offers unique opportunities for the development of redox-neutral transformations . Recently, we established that dual transition metal electrocatalysis is an effective platform for radical-based convergent paired electrolysis . Successful application of this convergent dual transition metal-based paired electrocatalysis requires the simultaneous activation and engagement of two transition metal catalysts at both electrodes, in which each catalyst independently operates on a respective redox event …”
Section: Introductionmentioning
confidence: 99%